Dynamic Performance Simulation and Experimental Research of Electric Vehicle Transmission System - Zhou Hongru; Sun Li; Song Jingbin (Jixie chuandong)
Based on the argument that transmission system parameter is a big consequence on electric vehicle dynamic performance,a parameter matching of electric vehicle is researched,which is aiming at vehicle dynamic performance and combining with the structure arrangement of transmission system. The integrated software Optimum lap with ADVISOR,the simulated model of transmission system is established by using second-level development,and the acceleration time test is conducted in straight roads,the strategy of parameter matching is validated by the simulation and experimental.